A green space between life and death – a case study of activities in Gamlebyen Cemetery in Oslo, Norway. Issue 1 (1st January 2016) - Swensen, Grete; Nordh, Helena; Brendalsmo, Jan
ABSTRACT: The amount of green space in urban areas is shrinking. Densification and the introduction of new user groups in most cities today is leading to more intensive use of public spaces and the need for more space. Urban cemeteries constitute a unique type of public space: while some may consider them primarily religious and contemplative spaces, others see them as primarily recreational or as heritage sites steeped in history. The authors examine the extent to which the pressure on cities' open green areas combined with influences from intercultural encounters is mirrored in the use and character of cemeteries today – exemplified by Gamlebyen Cemetery (Gamlebyen Gravlund) in Oslo, Norway. They used observations in combination with short semi-structured interviews with those using the cemetery. The findings of pilot study conducted in 2013 suggest that religious aspects played a minor role and that the recreational aspects were more important to most of the interviewees. Many of them considered that the cemetery provided a pleasant green walkway on their way to work, busses or city services. The cemetery offered a combination of calmness, an aesthetically pleasant environment, and 'cultivated nature' in an urban context, and was thus an arena that invited respect and esteem.